Family life in late periurban communities: Sociability and living conditions (Buenos Aires, Argentina: 1950-1970) - de Marco, Celeste (Universidad Pedagógica y Tecnológica de Colombia, 2016)
During the second half of the XXth century, Argentina went through the last attempts at a policy of long time tradition, known as agricultural colonization. Usually, lands in the pampa zone were selected, with a traditional productive and agro-export relevance. Nevertheless, certain periurban areas of the cities of Buenos Aires and La Plata became of interest because of their highly productive soil, their location near major urban centers, and their capacity to house families. These areas have not been studied carefully and need to be explored. With this study we look into the situation of the families that lived in this speciic context, addressing their multi-ethnic origins, trajectories, work methods, and social practices. With this purpose, we selected two communities: “La Capilla” (Florencio Varela, southern zone, Gran Buenos Aires) and “Justo José de Urquiza” (La Plata, capital city of the province). We found that these communities were consolidated by the formation of formal and informal societies, characterized by the participation of the families and subjects who contributed to the community through their roles and practical knowledge. It was found that children played a particularly important role as social subjects, articulating the different spaces in which their families lived.